Circulating CCN6/WISP3 in type 2 diabetes mellitus patients and its correlation with insulin resistance and inflammation: statistical and machine learning analyses - Reza Afrisham; Yasaman Jadidi; Nariman Moradi; Seyed Mohammad Ayyoubzadeh; Reza Fadaei; Omid Kiani Ghalesardi; Vida Farrokhi; Shaban Alizadeh (BMC Medical Informatics and Decision Making)
Abstract Introduction Cellular Communication Network Factor 6 (CCN6) is an adipokine whose production undergoes significant alterations in metabolic disorders. Given the well-established link between obesity-induced adipokine dysfunction and the development of insulin resistance and type 2 diabetes mellitus (T2DM), this study investigates the potential role of CCN6 as a biomarker for T2DM. The present study aimed to investigate the association between serum CCN6 levels and T2DM, as well as its risk factors, for the first time. Methods In this case-control study, a total of 80 individuals diagnosed with T2DM and 80 healthy control individuals, who referred to Shariati hospital (Tehran, Iran), were included in the study. Biochemical parameters including fasting blood glucose (FBG), aspartate transaminase (AST), alanine transaminase (ALT), triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) were determined using the AutoAnalyzer instrument. The circulating levels of CCN6, adiponectin, Tumor necrosis factor-α (TNF)-α, Interleukin 6 (IL-6), and insulin were quantified using ELISA. The Student t-test was applied to data that presented as mean ± standard deviations (SD). Moreover, the Gini Index was utilized to determine the weight of each factor in T2DM classification. Additionally, various machine learning models were employed to develop classifiers for predicting T2DM. Results T2DM patients demonstrated significantly lower levels of CCN6 (1259.76 ± 395.02 pg/ml) compared to controls (1979.17 ± 471.99 pg/ml, P < 0.001), as well as lower levels of adiponectin (P < 0.001) and higher levels of TNF-α and IL-6 (P < 0.001) compared to non-T2DM individuals. In the T2DM group, CCN6 exhibited negative correlations with insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), body mass index (BMI), IL-6, and TNF-α. Logistic regression analysis indicated an increased risk of T2DM, with a CCN6 cutoff value of 1527.95 pg/mL distinguishing T2DM patients with 86.3% sensitivity and 73.8% specificity. The Gini Index highlighted that HOMA-IR, IL6, and CCN6 had the highest weighting on T2DM. Conclusion Our research identified a significant and negative association between serum CCN6 levels and the likelihood of T2DM, as well as inflammation biomarkers (IL-6 and TNF-α). CCN6 shows promise as a potential biomarker for T2DM; however, further investigations are necessary to validate this finding and assess its clinical utility.